Baclofen: To screen or not to screen in postmortem blood? - Nahar,LK; Murphy,KG; Paterson,S (Journal of Analytical Toxicology, 2021)
Baclofen (BLF) has been prescribed in the UK since 1972 for the alleviation of spasticity. However, evidence suggests BLF is also recreationally misused. It has been associated with ethanol, gamma-hydroxybutyric acid (GHB), pregabalin (PGL) and gabapentin (GBP) use/abuse and deaths have been reported. With current postmortem (PM) toxicological screening approaches, BLF is not routinely included in the general drugs screen, and is only screened for if specifically mentioned in the case documents. The extent of BLF misuse is thus unclear. This study was carried out to determine the prevalence and concentrations of BLF in Coroners’ toxicology, to investigate whether BLF misuse with ethanol, GHB, PGL and GBP is causing death and to determine the potential extent of the under-reporting of BLF-associated deaths. Between 01/01/2016 to 31/12/2017, 3750 PM femoral vein bloods were screened for BLF; all positive cases were quantified. Only 0.56% of samples screened positive for BLF, with concentration ranging from 0.08 to 102.00 µg/mL (median = 0.28). It was determined that routine analysis without additional screening of BLF had been performed, 43% of BLF positives cases would have been missed. However, given the low incidence of detection, this only represents 0.25% of the cohort. Likely illicit use of BLF with GHB was seen in one case only. Death from the recreational use of BLF with PGL and GBP was not observed. Only two cases positive for BLF had an ethanol concentration of ≥ 50 mg%. Two cases of presumed intentional overdose of BLF were observed. This study highlights that although BLF abuse may be occurring, deaths are rare. It is therefore not cost or time effective to screen for BLF in all PM cases. With BLF currently being investigated for the treatment of alcoholism and withdrawal symptoms of illicit drug use, BLF-related deaths may rise in the future.